A review of ancient Egyptian pigments and cosmetics. (3rd July 2016) - Scott, David A.
Abstract : The pigments used by the ancient Egyptians constitute the most diverse pigment palette of the ancient world. This review discusses the pigments and binders which were used, arranged principally in terms of the colours themselves, namely, the white, green, grey, black, brown, blue, red, orange, and yellow pigments. The chemical identity of these pigments is discussed with some details regarding the artefacts or time periods from which the pigment concerned has been identified. Combinations of pigments were used for creating some colours, especially: greens, pinks, blues, yellows, and a variety of pale hues by mixing primary colours with a white addition, such as calcite. The identification of ancient Egyptian pigments is often aggravated by chemical interactions between pigment and binder media, or between the pigment and environmental pollutants, or both. The nature of the binders and varnishes used in ancient Egypt is briefly discussed. The identification of green pigments from ancient Egypt is often difficult, and some of the recent research concerning the topic is reviewed. In addition to including relevant details from older literature, this review provides a synopsis of recent studies which have appeared since the last major review carried out by Lee and Quirke in 2000.